Ischaemic heart disease, influenza and influenza vaccination: a prospective case control study. Issue 24 (21st August 2013) - MacIntyre, C Raina; Heywood, Anita E; Kovoor, Pramesh; Ridda, Iman; Seale, Holly; Tan, Timothy; Gao, Zhanhai; Katelaris, Anthea L; Siu, Ho Wai Derrick; Lo, Vincent; Lindley, Richard; Dwyer, Dominic E
Abstract : Background: Abundant, indirect epidemiological evidence indicates that influenza contributes to all-cause mortality and cardiovascular hospitalisations with studies showing increases in acute myocardial infarction (AMI) and death during the influenza season. Objective: To investigate whether influenza is a significant and unrecognised underlying precipitant of AMI. Design: Case-control study. Setting: Tertiary referral hospital in Sydney, Australia, during 2008 to 2010. Patients: Cases were inpatients with AMI and controls were outpatients without AMI at a hospital in Sydney, Australia. Main outcome measures: Primary outcome was laboratory evidence of influenza. Secondary outcome was baseline self-reported acute respiratory tract infection. Results: Of 559 participants, 34/275 (12.4%) cases and 19/284 (6.7%) controls had influenza (OR 1.97, 95% CI 1.09 to 3.54); half were vaccinated. None were recognised as having influenza during their clinical encounter. After adjustment, influenza infection was no longer a significant predictor of recent AMI. However, influenza vaccination was significantly protective (OR 0.55, 95% CI 0.35 to 0.85), with a vaccine effectiveness of 45% (95% CI 15% to 65%). Conclusions: Recent influenza infection was an unrecognised comorbidity in almost 10% of hospital patients. Influenza did not predict AMI, but vaccination was significantly protective but underused. The potential population health impact of influenza vaccination, particularly in the age group 50–64 years, who are at risk for AMI but not targeted for vaccination, should be further explored. Our data should inform vaccination policy and cardiologists should be aware of missed opportunities to vaccinate individuals with ischaemic heart disease against influenza.